Investigating the Insecticidal Properties of Alangium salviifolium Root Extracts on Culex quinquefasciatus Mosquitoe - Yagoo, Alex; Milton, M.C. John; Vilvest, Jelin (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
This study evaluated the effectiveness of successive hexane, chloroform, and methanol extracts of Alangium salviifolium roots in combating mosquito-borne diseases caused by Culex quinquefasciatus mosquitoe in India. The hexane extract showed the highest efficacy with LC50 values of 105.0 ppm (larvicidal activity), 108.0 ppm (pupicidal activity), and 65.6 ppm (ovicidal activity). The chloroform extract had LC50 values of 156.8 ppm (larvicidal), 376.0 ppm (pupicidal), and 20.0 ppm (ovicidal), while the methanol extract had LC50 values of 235.7 ppm (larvicidal), 441.8 ppm (pupicidal), and 30.4 ppm (ovicidal). The hexane extract of A. salviifolium roots shows potential as a mosquito control agent, specifically against Cx. quinquefasciatus mosquitoes. Further studies are needed to assess the safety and effectiveness of this extract. This research highlights the potential of plant extracts as alternative mosquito control agents for mitigating mosquito-borne diseases in India.